ANALISIS KEHANDALAN STRUKTUR BANGUNAN WISMA ATLIT RAGUNAN PASCA KEBAKARAN - Muhammad Rusli (Widyariset, 2009)
The data acquisition of the post-fire construction is done by visual observation, dimension measure-ment, concrete field testing and also laboratory testing. Visual observation above the third floor which is directly on fire, indicate serious damages with the result that all of the building component above the third floor must be replaced by a new construction. The testing of building material shows that the grade of concrete component which is directly fired has fc '=6.8 MPa, while the non-fired component has fc'=15.2 MPa. The structural analysis shows that most of the building components at the first and the second floor are able to be functioned with a little repair of longitudinal balk at their support section to increase bending capacities.